An economic evaluation of mass population screening for colorectal cancer using a faecal occult blood test - Walker, Andrew (1993)
Cancer of the colon and rectum is a major cause of ill-health. Options for reducing the burden of the disease include primary prevention, screening for early stage asymptomatic disease and improvements in the treatment of symptomatic disease. If the policy objective is to make a major impact on mortality from the disease then screening appears to be the only technically feasible option.